Bio-ecology of Slender Black Rice Bug, Paraeucosmetus pallicornis in South Sulawesi - Rahmini, Rahmini; Munawar, Dede; Senoaji, Wasis; Baliadi, Yuliantoro (KnE Life Sciences, 2017)
A study on the bio-ecology of slender black rice bug, Paraeucosmetus pallicornis, was conducted in the research farm of Lolit Tungro, Lanrang, South Sulawesi, Indonesia. This pest is considered as new rice pest, attacking rice plant especially during generative stage. This pest inserts its stylet and then sucks the sap of the developing rice grain. Light trap was used to catch this pest. Yellow sticky trap and pitfall trap were used to determine the insect population and to find out when the pest infests the plant. Fifteen yellow sticky traps were set diagonally on rice field, and 10 pitfall traps were placed on the ground. The traps were placed on three plots as replication. On the first week of the study, it was found that the number of captured insects from the light trap during harvesting was 193. On the 2nd to 4th weeks, during fallow stubble, the captured insects were 135 -740. In the early of May, the field started to be ploughed as preparation for the next planting season. As the result, the number of insects captured decreased to 53 – 152 insects. The 2013 planting season was started in June. During this period, the bugs captured were only 1 – 3. This indicates that the bugs have already moved or migrated out of the rice field. The average number of eggs laid were 53.3 (1 pair), 124.8 (2 pairs), 142.5 (3 pairs), 202.3 (4 pairs), and 284 (5 pairs) and the average of hatch rate was 29.9%. The damaged rice grain was 38% grains/panicle (ranged 24.2-57.4%). This level of damage indicates that the P. pallicornis contributes to the reduction of rice yield. Keywords: Paraeucosmetus pallicornis, rice pest